Estimation of the resonance frequency of rotational and translational signals evoked by mining-induced seismicity - Nawrocki, Dariusz; Mendecki, Maciej J.; Teper, Leslaw (Frontiers in Earth Science, 2024)
The horizontal-to-vertical (H/V) method is a fundamental fast tool to estimate local site effect parameters by using the registered signals of the translational motion. The spectral ratio is mostly calculated using the Fourier Spectrum Analysis (FSA), which may lead to problems with accurate resonant frequency determination due to evident multi-amplification peaks occurrence on the spectrum. Alternatively the H/V ratio may be estimated by use Response Spectrum Analysis (RSA), where only a general amplification peak is expected. However, the fundamental limitations of the RSA assumption are related to the real impact of the events’ scenario dependence (i.e., magnitude, distance, focal mechanism, etc.). The limitations and advantages of the RSA and FSA are commonly known in the case of the analysis performed for the translational signals. Therefore, the critical question is: should the RSA and FSA methods be used to estimate the H/V ratio of the recorded rotational signals of the events? The article presents horizontal-to-vertical (H/V) spectral ratios calculated for rotational and translational signals registered as an effect of mining-induced seismicity by four independent seismic stations located in Poland's Upper Silesian Coal basin. The spectral ratios of the signals were estimated using the RSA and the FSA method. The studies show that in the case of translational motion, the H/V estimations using the RSA derived clear information of the resonant frequency peak, confirming the method’s usefulness in the case of multi-amplification peaks. The opposite situation was noticed in the case of the rotational motion. The derived H/V spectrum, using the RSA, produced single amplification peaks for the seismic stations, where the sensors were mounted on a small floor at a significant distance from the walls. In cases where the sensors were deployed on the building floor, a decrease in the reliability of the RSA and the FSA method was noticed. The results of the studies suggested that the possibility of the estimations of the H/V spectrum using the RSA and FSA algorithm is strongly limited for rotational motions due to the size of the floor and distance to the building walls where the sensors were mounted. The explanation of that fact is related to the effects of kinematic soil-structure interaction, which may significantly affect rotational measurements due to the tendency to obtain higher frequency content than in the case of the translations. Consequently, the values of the Z- component of the rotational motion may be lovered than in the free-field measurements, decreasing the reliability of the H/V estimations for rotational motion.